Dvarashakha (architrave) of the Garbhagriha of the side shrine - Temples of India Project Team (Jio Institute, 2024)
The dvarashakha (architrave) of the garbhagriha (sanctum sanctorum) of the side shrine, in the Triple-shrine Temple, is an ornamental feature. It is a trishakha (three vertical bands) variety of which the innermost shakha (band or branch) has a depiction of ganas (celestial beings), next to which is mithuna shakha (band of amorous couples), and the outermost is a patra shakha (foliage band). The threshold of this dvarashakha has foliage motifs flanked by vyalas (composite mythical animal creatures). The lower portion of the dvarshakha has a depiction of attendants and river goddesses. Vishnu on his mount Garuda is depicted on the lintel of the dvarashakha.